2020
DOI: 10.22271/chemi.2020.v8.i5y.10564
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of browntop millet as influenced by dates of sowing and nitrogen levels

Abstract: A field experiment was conducted during kharif, 2019 at College Farm, College of Agriculture, Rajendranagar, Hyderabad to study the effect of dates of sowing and nitrogen levels on growth and yield of browntop millet. The experiment was laid out in factorial randomized block design with 16 treatment combinations and replicated thrice. The treatments consisted of four dates of sowing viz., D1-June 15 th , D2-June 30 th , D3-June 15 th , D4-July 30 th and four nitrogen levels viz., N1-0 kg ha -1 , N2-20 kg ha -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Consequently, the crops were able to fully express their genetic potential, leading to active photosynthesis and enhanced translocation of assimilates to the reproductive parts. This observation aligns with previous studies conducted by Maurya et al (2016), Gavit et al (2017) and Saikishore et al (2020).…”
Section: Influence Of Dates Of Sowing On Yield Of Kodo Milletsupporting
confidence: 94%
“…Consequently, the crops were able to fully express their genetic potential, leading to active photosynthesis and enhanced translocation of assimilates to the reproductive parts. This observation aligns with previous studies conducted by Maurya et al (2016), Gavit et al (2017) and Saikishore et al (2020).…”
Section: Influence Of Dates Of Sowing On Yield Of Kodo Milletsupporting
confidence: 94%
“…These factors allowed the crop to reach its full potential, which included increased assimilation in the reproductive parts and active photosynthesis. Similar findings were reported by Amanullah et al (2015), Maurya et al (2016), Gavit et al (2017) and Saikishore et al (2020). The data presented in Table 3 revealed that higher gross returns, net returns and B:C ratio were recorded in crop sown during first fortnight of July (` 76508 ha -1 , ` 45778 ha -1 and 2.49, respectively) followed by second fortnight of July (` 72896 ha -1 , ` 42166 ha -1 and 2.37, respectively).…”
Section: Effect Of Dates Of Sowingsupporting
confidence: 90%
“…BTM is drought-tolerant, early maturing and harvested in about 75-80 days earlier than other millets. This millet is well suited for dry land, grown under a variety of soils and climates (Kishore et al, 2020(Kishore et al, , 2021.…”
Section: Usesmentioning
confidence: 99%